2018
DOI: 10.1002/app.46329
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes/polyaniline nanocomposite coatings: Preparation, rheological behavior, and their application in paper surface treatment

Abstract: Conventional cellulosic paper, rendered electro-conductive, may hold considerable promise for diversified applications in such areas as electro-magnetic interference shielding and energy storage. Here, an electro-conductive cellulosic paper was prepared by surface application of multi-walled carbon nanotubes (MWCNTs)/polyaniline (PANI) nanocomposites onto a conventional base paper. MWCNTs/PANI nanocomposites were prepared by in situ polymerization of aniline with different contents of MWCNTs and used as electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our results corroborate those of Huang et al 56 who noticed an increase in the tensile index of PVA/cellulose nanofibers coated paper when cellulose nanofibers (CNFs) content was increased to 3.0 wt%, most likely due to the ability of the incorporated CNFs to interact through their hydroxyl groups with fibers on the surface of paper leading to the enhancement of bonding force between the cellulosic fibers, thus improving the tensile strength of the resulting nanocomposite papers. Similar behavior was previously noticed by Mao et al 57 who reported a percentage increase of 12.46% in the tensile index of nanocomposite multi-walled carbon nanotubes (MWCNTs)/polyaniline (PANI) nanocomposites coated paper as a result of increasing MWCNTs content as compared to the base paper. Such improvement in the mechanical strength of the resulting coated papers was mainly attributed to the excellent reinforcing effect of incorporating nanofillers along with the ability of MWCNTs and PANI to form a core–shell structure that may confer external force to the whole system, leading to the improvement of the mechanical properties of surface-coated paper.…”
Section: Resultssupporting
confidence: 87%
“…Our results corroborate those of Huang et al 56 who noticed an increase in the tensile index of PVA/cellulose nanofibers coated paper when cellulose nanofibers (CNFs) content was increased to 3.0 wt%, most likely due to the ability of the incorporated CNFs to interact through their hydroxyl groups with fibers on the surface of paper leading to the enhancement of bonding force between the cellulosic fibers, thus improving the tensile strength of the resulting nanocomposite papers. Similar behavior was previously noticed by Mao et al 57 who reported a percentage increase of 12.46% in the tensile index of nanocomposite multi-walled carbon nanotubes (MWCNTs)/polyaniline (PANI) nanocomposites coated paper as a result of increasing MWCNTs content as compared to the base paper. Such improvement in the mechanical strength of the resulting coated papers was mainly attributed to the excellent reinforcing effect of incorporating nanofillers along with the ability of MWCNTs and PANI to form a core–shell structure that may confer external force to the whole system, leading to the improvement of the mechanical properties of surface-coated paper.…”
Section: Resultssupporting
confidence: 87%
“…By contrast, at high frequencies, Gʹ and G˝are dependent on the frequency and both increase with increasing frequency, as the structure of the inks does not have enough time to relax [40]. Moreover, there is a gradual rise in tanδ with increasing GS content as a result of the increased viscosity of inks [41]. These results are contributed to the storage and screen printing of composite inks: the inks have higher elasticity in the static state and higher viscosity during printing.…”
Section: Resultsmentioning
confidence: 98%
“…The combination of conductive polymer and carbon also has been found to improve the conductivity of cellulosic substrates. Mao et al (2018) studied the coating of carbon nanotubes/polyaniline nanocomposite layers on cellulosic paper and found that the conductivity of electro-surface-coated paper could reach 46.4 S/cm when the CNTs content was 10 wt %.…”
Section: Combinationsmentioning
confidence: 99%